2009
DOI: 10.1002/biof.47
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian NDR/LATS protein kinases in hippo tumor suppressor signaling

Abstract: The NDR/LATS family of kinases is a subgroup of the AGC group of protein kinases and is conserved from lower eukaryotes to humans. Like other AGC kinases, NDR/LATS kinases require phosphorylation of conserved Ser/Thr residues for activation. On the one hand, binding of the coactivator MOB to NDR/LATS allows autophosphorylation. On the other hand, MST kinases directly phosphorylate NDR/LATS kinases. In addition to our understanding of the molecular activation mechanisms, recent studies have shown that LATS kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 74 publications
(218 reference statements)
1
82
0
Order By: Relevance
“…Activated LATS1/2 phosphorylate YAP, which inhibited cell proliferation in mammalian cells 38, 39, 40. In confirmation that WWC2 activates the Hippo pathway in HCC, overexpression of WWC2 in SMMC‐7721 cells (which express low levels of WWC2) increased phosphorylation of both LATS and YAP, which has been previously shown to negatively regulate the Hippo pathway 11, 41, 42. The latter study also revealed HCC cells transfected with the WWC2 overexpression plasmid decreased the mRNA level of Cyr61 and CTGF, both which are the target genes of Hippo pathway.…”
Section: Discussionmentioning
confidence: 57%
“…Activated LATS1/2 phosphorylate YAP, which inhibited cell proliferation in mammalian cells 38, 39, 40. In confirmation that WWC2 activates the Hippo pathway in HCC, overexpression of WWC2 in SMMC‐7721 cells (which express low levels of WWC2) increased phosphorylation of both LATS and YAP, which has been previously shown to negatively regulate the Hippo pathway 11, 41, 42. The latter study also revealed HCC cells transfected with the WWC2 overexpression plasmid decreased the mRNA level of Cyr61 and CTGF, both which are the target genes of Hippo pathway.…”
Section: Discussionmentioning
confidence: 57%
“…Considering that all core components of MEN/SIN and Hippo signalling are conserved from yeast to humans [15,16,73], one might expect that research has already established that a signalling cascade composed of MST1/2 kinases (the human counterpart of Hippo), LATS/ NDR kinases (the human analogues of Lats/Trc), and hMOB1 (the human version of Mats) is essential for mitotic exit and cytokinesis. However, somewhat similar to our current picture of mitotic Hippo signalling in Drosophila (see Section 4), our understanding of mammalian Hippo signalling in mitosis is limited (Fig.…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 99%
“…Merlin, Mst1/2, and LATS1/2) or oncogenes (e.g. YAP and its paralog TAZ) (for detailed reviews, see references [22,[26][27][28][29][30][171][172][173]). Together, these studies strongly suggest that dysregulation of size control may be important in the development of human cancers.…”
Section: Cancermentioning
confidence: 99%